The Effectiveness of Outdoor Learning to Improve English Skills at Aceh Islamic Nature School (AINS) - Putra, Rahmad Syah; Khatami, M; Kurniawan, Rahmat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The existence of outdoor learning that began to be carried out by nature schools became an exciting learning method. This outdoor learning activity raises interest in students' enthusiasm for learning because students get new experiences and discover new things. This study used a qualitative method and was conducted at the Aceh Islamic Nature School (AINS) by examining students' understanding of English using outdoor learning. Data collection techniques were carried out by observing and interviewing English teachers at the school. As a finding, learning English with outdoor learning methods has various ways, such as inviting students to know directly in English. For each material, a song is sung together so they can remember the lesson and the material studied. Outdoor learning at AINS also has adequate supporting factors, such as the provision of vocabulary stickers on the walls of spaces/objects. The teacher gets used to speaking in English to improve students' listening so that they are used to it and can respond. Based on these results, From the data based on observations, interviews, and document analysis above, outdoor learning by inviting students to see material objects directly from nature is considered effective. What teachers apply with this method to students is successfully meeting all kinds of targets for each material, especially in increasing English language skills, which can be seen from their mastery of vocabulary. Apart from that, outdoor learning is also considered to prevent students from getting bored quickly and being enthusiastic about following all the material the teacher provides.